Comparison of tunnel and VISTA techniques for multiple gingival recession treatment: A systematic literature review - Ksenija Matvijenko; Rokas Borusevičius (Journal of Advanced Periodontology and Implant Dentistry)
Background. Gingival recession (GR) has become one of the most common concerns in oral mucosal diseases. It causes discomfort such as root hypersensitivity, root caries, and aesthetic problems, leading to the development of various surgical techniques to address GRs. This study compared the non-advanced tunnel and m-VISTA techniques in treating multiple GRs. Methods. A literature search related to the efficiency of non-advanced tunnel and m-VISTA techniques was conducted in MEDLINE (PubMed), EMBASE (ScienceDirect), Cochrane Central Register of Controlled Trials (Cochrane Library), Springer Link, and Google Scholar. Randomized controlled trials (RCTs) reporting periodontal parameters published in the recent four years (2019–2023) were included and assessed for the risk of bias. All in vitro, animal, pilot studies, case reports, and case series were excluded. Results. Five RCTs were included with 195 cases of GRs. Comparing the two techniques revealed a significant increase in keratinized tissue width (KTW) from baseline to 6 months (-1.4 mm), in clinical attachment level (CAL) (-2.65 mm), and in recession depth (-2.7 mm) for the tunnel technique. On the other hand, a significant increase in GR width (-2.26 mm) was found in the m-VISTA group. Finally, there were no significant differences in probing depths. Conclusion. Both techniques were effective in root coverage and may be valuable for treating multiple GRs.